Epithelial expression and function of trypsin-3 in irritable bowel syndrome. Issue 10 (17th January 2017) - Rolland-Fourcade, Claire; Denadai-Souza, Alexandre; Cirillo, Carla; Lopez, Cintya; Jaramillo, Josue Obed; Desormeaux, Cleo; Cenac, Nicolas; Motta, Jean-Paul; Larauche, Muriel; Taché, Yvette; Berghe, Pieter Vanden; Neunlist, Michel; et al.
Abstract : Objectives: Proteases are key mediators of pain and altered enteric neuronal signalling, although the types and sources of these important intestinal mediators are unknown. We hypothesised that intestinal epithelium is a major source of trypsin-like activity in patients with IBS and this activity signals to primary afferent and enteric nerves and induces visceral hypersensitivity. Design: Trypsin-like activity was determined in tissues from patients with IBS and in supernatants of Caco-2 cells stimulated or not. These supernatants were also applied to cultures of primary afferents. mRNA isoforms of trypsin ( PRSS1, 2 and 3 ) were detected by reverse transcription-PCR, and trypsin-3 protein expression was studied by western blot analysis and immunohistochemistry. Electrophysiological recordings and Ca 2+ imaging in response to trypsin-3 were performed in mouse primary afferent and in human submucosal neurons, respectively. Visceromotor response to colorectal distension was recorded in mice administered intracolonically with trypsin-3. Results: We showed that stimulated intestinal epithelial cells released trypsin-like activity specifically from the basolateral side. This activity was able to activate sensory neurons. In colons of patients with IBS, increased trypsin-like activity was associated with the epithelium. We identified that trypsin-3 was the only form of trypsin upregulated in stimulated intestinal epithelial cells and in tissues from patients with IBS. Trypsin-3 was able to signal to human submucosal enteric neurons and mouse sensory neurons, and to induce visceral hypersensitivity in vivo, all by a protease-activated receptor-2-dependent mechanism. Conclusions: In IBS, the intestinal epithelium produces and releases the active protease trypsin-3, which is able to signal to enteric neurons and to induce visceral hypersensitivity.